THE MEANING OF RA’Y AND NATURE OF ITS USAGE IN ISLAMIC LAW (An Examination of Select cases of the Legal Reasoning in the Period of ’Umar, the Second Caliph) - Shafiq, Muhammad (Islamic Studies, 1984)
N/A